Viral skin infections - Cyr, P. R. (The Physician and Sportsmedicine, 2004)
Viral skin infections, such as herpes simplex, molluscum contagiosum, and warts, are common in athletes. Visual inspection alone can often provide a diagnosis. The Tzanck test or a direct fluorescent antibody test for herpes simplex virus 1 and 2 can also establish an early diagnosis. If prevention strategies fail, early detection and treatment will help limit the spread of viral infections to other teammates. National Collegiate Athletic Association rules prohibit participation by players who have herpes virus infections unless they are properly treated; lesions of molluscum contagiosum and warts must be treated or securely covered before return to play in contact sports.